The Affirmation of Life in Wallace Stevens' "The Auroras of Autumn" and T.S. Eliot's Four Quartets - Lipes, Jesse (Wake Forest University, 2012)
My thesis traces the affirmation of life evident in Wallace Stevens' "The Auroras of Autumn" and T.S. Eliot's Four Quartets, defining the term affirmation by the expansive embrace of suffering demonstrated by Alyosha Karamazov in Fyodor Dostoevsky's The Brothers Karamazov. I maintain that, similar to Alyosha, Stevens affirms life by acknowledging the inevitability of change, established by the ceaseless passage of time, and by celebrating human existence while recognizing the paradoxical positive and negative effects suffering exerts on individuals. Also, similar to Alyosha's affirmation, in Four Quartets, Eliot frequently concentrates on the inevitability and instrumentality of suffering--its unique power to shape an individual's character into someone who "fructifies in the lives of others." Thus, he too maintains the same foundation of unconditional embrace and joy. In Four Quartets, I contend that Eliot affirms life by proclaiming that individuals must be fully engrossed, including mind and body, in the immediacy of each successive moment, regardless of whatever potential threats it may pose. Additionally, in each chapter, I explore in greater detail the various elements that each poet identifies as detracting from humanity's ability to affirm life. In short, Stevens faults the pressure of news and excessive reliance on history for obscuring the fundamental innocence of existence, and the constant transformation it experiences. For Stevens, if humanity recognized this innocence and inexorable change, they would insert themselves into the natural process of affirmation embodied by the earth; they would constantly seek new experiences and revitalizing resemblances. For Eliot, the fear and anxiety of living in the present--of not knowing the future--blocks affirmation.
Keywords: affirmation of life; Auroras of Autumn; Four Quartets; Modern poetry; TS Eliot; Wallace Stevens